Trust chain management model based on recommendation - TIAN Jun-feng; LU Yu-zhen; LI Ning (Tongxin xuebao)
Aiming at the present problem that the trust information was not sufficient when processing the trust com-putation in trust link management,a recommendation based trust chain management model（RTCM） was presented.With the building of the trusted network,considering the factors such as the transition fading,time decay,and weight of the path and so on,the model decreased the time complexity in the search of the trusted paths.Used weighted closeness to combine the recommendation paths,fully considered the trust-related information,and the policy to in-hibit the malicious recommendation was given.Finally,the experiment has shown that this model has improved the trustworthiness of network.